AVATAR Assesses Speech Understanding and Multitask Costs in Ecologically Relevant Listening Situations. Issue 3 (May 2020) - Devesse, Annelies; van Wieringen, Astrid; Wouters, Jan
Abstract : Objectives: There is a high need among clinicians and researchers for an ecologically valid measure of auditory functioning and listening effort. Therefore, we developed AVATAR: an "Audiovisual True-to-life Assessment of Auditory Rehabilitation" which takes important characteristics of real-life listening situations into account, such as multimodal speech presentation, spatial separation of sound sources and multitasking. As such, AVATAR aims to assess both auditory functioning and the amount of allocated processing resources during listening in a realistic yet controllable way. In the present study, we evaluated AVATAR and investigated whether speech understanding in noise and multitask costs during realistic listening environments changed with increasing task complexity. Design: Thirty-five young normal-hearing participants performed different task combinations of an auditory-visual speech-in-noise task and three secondary tasks on both auditory localization and visual short-term memory in a simulated restaurant environment. Tasks were combined in increasing complexity and multitask costs on the secondary tasks were investigated as an estimate of the amount of cognitive resources allocated during listening and multitasking. In addition to behavioral measures of auditory functioning and effort, working memory capacity and self-reported hearing difficulties were established using a reading span test and a questionnaire on daily hearing abilities. Results: Whereas performance on the speech-in-noise task was not affected by task complexity, multitask costs on one of the secondary tasks became significantly larger with increasing task complexity. Working memory capacity correlated significantly with multitask costs, but no association was observed between behavioral outcome measures and self-reported hearing abilities or effort. Conclusions: AVATAR proved to be a promising model to assess speech intelligibility and auditory localization abilities and to gauge the amount of processing resources during effortful listening in ecologically relevant multitasking situations by means of multitask costs. In contrast with current clinical measures of auditory functioning, results showed that listening and multitasking in challenging listening environments can require a considerable amount of processing resources, even for young normal-hearing adults. Furthermore, the allocation of resources increased in more demanding listening situations. These findings open avenues for a more realistic assessment of auditory functioning and individually tuned auditory rehabilitation for individuals of different age and hearing profiles.